The Combined Use of Melatonin and an Indoleamine 2,3-Dioxygenase-1 Inhibitor Enhances Vaccine-Induced Protective Cellular Immunity to HPV16-Associated Tumors - Moreno, Ana C. R.; Porchia, Bruna F. M. M.; Pagni, Roberta L.; Souza, Patrícia da Cruz; Pegoraro, Rafael; Rodrigues, Karine B.; Barros, Tácita B.; Aps, Luana R. de Melo Moraes; de Araújo, Eliseu F.; Calich, Vera L. G.; Ferreira, Luís C. de Souza (Frontiers in Immunology, 2018)
Immunotherapy has become an important ally in the fight against distinct types of cancer. However, the metabolic plasticity of the tumor environment frequently influences the efficacy of therapeutic procedures, including those based on immunological tools. In this scenario, immunometabolic adjuvants arise as an alternative toward the development of more efficient cancer therapies. Here we demonstrated that the combination of melatonin, a neuroimmunomodulator molecule, and an indoleamine 2,3-dioxygenase (IDO) inhibitor (1-methyl-DL-tryptophan, DL-1MT) improves the efficacy of an immunotherapy (gDE7) targeting human papillomavirus (HPV)-associated tumors. Melatonin or IDO inhibitors (D-1MT and DL-1MT) directly reduced proliferation, migration, adhesion and viability of a tumor cell line (TC-1), capable to express the HPV-16 E6 and E7 oncoproteins, but could not confer in vivo antitumor protection effects. Nonetheless, combination of gDE7 with melatonin or D-1MT or DL-1MT enhanced the antitumor protective immunity of gDE7-based vaccine in mice. Notably, expression of IDO1 in stromal cells and/or immune cells, but not in tumor cells, inhibited the antitumor effects of the gDE7, as demonstrated in IDO1-deficient mice. Finally, co-administration of gDE7, melatonin and DL-1MT further improved the protective antitumor effects and the numbers of circulating E7-specific CD8+ T cells in mice previously transplanted with TC-1 cells. The unprecedented combination of melatonin and IDO inhibitors, as immunometabolic adjuvants, thus, represents a new and promising alternative for improving the efficacy of immunotherapeutic treatments of HPV-associated tumors.